Mutations in MEGF10, a regulator of satellite cell myogenesis, cause early onset myopathy, areflexia, respiratory distress and dysphagia (EMARDD) - Logan, Clare V; Lucke, Barbara; Pottinger, Caroline; Abdelhamed, Zakia A; Parry, David A; Szymanska, Katarzyna; Diggle, Christine P; van Riesen, Anne; Morgan, Joanne E; Markham, Grace; Ellis, Ian; Manzur, Adnan Y; et al. (Nature genetics, 2011)
Markus Schuelke, Colin Johnson and colleagues report the identification of mutations in MEGF10 that cause infantile myopathy with diaphragmatic weakness, areflexia, respiratory distress and dysphagia. Infantile myopathies with diaphragmatic paralysis are genetically heterogeneous, and clinical symptoms do not assist in differentiating between them. We used phased haplotype analysis with subsequent targeted exome sequencing to identify MEGF10 mutations in a previously unidentified type of infantile myopathy with diaphragmatic weakness, areflexia, respiratory distress and dysphagia. MEGF10 is highly expressed in activated satellite cells and regulates their proliferation as well as their differentiation and fusion into multinucleated myofibers, which are greatly reduced in muscle from individuals with early onset myopathy, areflexia, respiratory distress and dysphagia.